Peningkatan Pengetahuan Lansia Melalui Edukasi Gizi Tentang Dietary Acid Load Untuk Pencegahan Penyakit Ginjal Kronis Di Wilayah Kerja Puskesmas Pauh Kota Padang - Faza Yasira Rusdi; Deni Elnovriza; Arif Sabta Aji; Dwifa Aprilia Putri; Rahmi Safitri (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2025)
Chronic Kidney Disease (CKD) is a health problem that continues to increase at the national and global levels. In West Sumatra Province, the prevalence of CKD is higher than the national average. It tends to increase along with the increase in cases of hypertension, diabetes mellitus, and unhealthy lifestyles. The Pauh Community Health Center is one of the areas with a high number of cases of hypertension and diabetes mellitus. However, there are no outreach activities regarding Dietary Acid Load (DAL) as a nutritional risk factor for CKD. This community service activity aimed to improve public awareness and knowledge about nutritional risk factors for CKD and to encourage healthy lifestyle behavior changes. The activity employed an educational approach through an interactive counseling method, using PowerPoint and leaflets as teaching aids. The participants consisted of 12 members of the Prolanis program. The average pre-test score was 5.6, while the average post-test score was 7.3, showing an increase of 1.7 points compared to the pre-test. Evaluation results indicated a significant improvement in participants’ knowledge regarding nutritional risk factors for CKD (p-value = 0.014). Regular nutrition education for Prolanis participants is recommended as part of CKD prevention efforts. In addition, the developed leaflet can be distributed to patients visiting Pauh Community Health Center daily.